Masters Nursing Students’ Perceptions of an Innovative Simulation Education Experience - Kelly, Michelle; Fry, M. (2013)
Background: Simulation was introduced into a master of nursing course, embedded within patient safety and clinical practice contexts. Student groups developed, enacted, and debriefed simulation scenarios from lived experiences. The study aimed to explore masters students' perceptions of the innovative simulation education strategy. Method: A 2-year qualitative, exploratory study retrospectively analyzed students' written reflections about the innovative educational strategy and application of simulation for clinical practice. Results: The study enrolled 21 participants. Five themes emerged from the analysis: a new awareness of the extent and range of simulation activities; building teams and meaningful work; supported, realistic, and extended learning; sharing and reconstructing “clinical stories”; and using simulation in practice. Conclusion: Masters nurses highly valued the innovative simulation education strategy to develop authentic scenarios and identified a wide range of clinical applications and ways to initiate simulation in the workplace.